Homodyne state tomography with photon number resolving detectors - Puentes, G; Lundeen, J; Branderhorst, M; Coldenstrodt-Ronge, H; Smith, B; Walmsey, I; IEEE (2008)
We introduce a complete tomographic reconstruction scheme geared toward low photon-number states. To demonstrate this method we reconstruct various single-mode coherent states. © 2008 Optical Society of America.